KEBIJAKAN PUBLIK TENTANG PENGGUNAAN TANAH PADA PEMBANGUNAN DAERAH : EVALUASI TERHADAP PEMBANGUNAN PERUMAHAN (STUDI KASUS DI KECAMATAN SUMBERSARI - JEMBER) - Djoko Purwanto; Caesaria Anggita Pitaloka; Fajar Dwi Setiawan (Universitas Muhammadiyah Jember, 2021)
Sumbersari District is a densely populated City District and is the center of education in Jember Regency. At least in Sumbersari District, there are one SMPN, two SMANs and four State Universities. So it is not surprising that the use of land as a regional development in the evacuation of housing development is mostly carried out in the District of Sumbersari, Jember. The use of land in regional development is an option that does not need to be eliminated, but significant solutions must be sought: how to reduce the various impacts that occur as a result of development and how to prevent the environment and natural resources from becoming damaged and depleted (unsustainable) in the programreaching a level growth. Every development carried out in an area must be directed, so that it is balanced, harmonious, efficient, effective, cultured and sustainable in order to improve the welfare of the people with justice. For that, it is necessary to formulate a plan called a spatial plan. Spatial plans that are national in nature, meaning that they